High Power Sinusoidal Generator With Use Of Pcm-Pwm Converter - Rozum, Stanislav (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
This paper deals with the study of generating a sinusoidal signal with output power up to hundreds of watts. Selected microcontroller calculates sinusoidal data which are used as the input for PWM module. Four outputs of the module directly drive four transistors of H bridge which ensures high output power. Purposed method of calculating integer sinusoidal samples allows changing the frequency at any time with minimal latency.
Keywords: sinusoidal generator; Class-D amplifier; fast calculation of sine function